Effect of Set Size on the Yield of Onion Under Libyan Conditions - EL-SHAFIE, M. W. (The Libyan Journal of Agriculture, 2023)
The present study was conducted in a randomized complete block design with four replicates in 1976-1977, and 1977-1978 seasons in Tripoli. Three sizes of sets: small, medium and large of Giza Synthetic cultivar were used. Data were statistically analysed. The results showed that small sets significantly produced greater weight of marketable yield and higher percentage of single bulbs than those resulted from either medium or large sets. Medium sets were superior to large ones. Large sets significantly produced higher percentage of bolters and greater number of sprouts than those produced by either medium or small sets. With respect to percentages of doubles and stand, there were no significant difference between the three set sizes. Medium and large sets decreased weight of marketable yield and percentage of single bulbs through the production of higher percentage of bolters. Under Libyan conditions, the use of small sets of Giza Synthetic reduced the percentage of bolters significantly.